Study of "Temporal hybridity” in The God of Small Things by Arundhati Roy - Gill, Navjot (Innovative Research Thoughts, 2018)
The topic of this essay is the investigation of literary translation's expressiveness phenomena. As far as English-Russian translation is concerned, the study's goal is to pinpoint the expressive methods used in A. Roy's book The God of Small Things and their thanatological characteristics axiological, emotional, and cultural meanings depict pictures that appear ubiquitous to Indian and Russian civilizations, according to the findings of the research. Translators may communicate expressive methods in the TT and accomplish their desired pragmatic impact in this way.. It is also possible to reduce cultural and axiological components since some linguistic cues have distinct cultural implications and are indicated to elicit certain emotional responses from those who are familiar with or knowledgeable about the source language culture. Differences in the formal systems of the source language and the destination language might predispose seme reduction. Content and comparative analyses of the source and target texts are the primary research approaches used in this study.